Nutritional analysis of the School Feeding Program menus offered in a municipality of Pará - Valente Leão, Paula; Dias, Rosa Maria; Ferreira Frazão, Andrea das Graças; Dias, Ivanira Amaral; Rosaulem Pereira da Silva, Isameriliam; Fernandes Corrêa, Nádia Alinne; Tavares Dutra Cavalcanti, Cláudia Daniele (O Mundo da Saúde, 2018)
The National School Feeding Program (PNAE) is a policy that aims to contribute to the improvement of school feeding. Therefore, the goal of this study was to analyze the menus offered in the year 2014 in public schools of the municipal and state educational network in the municipality of Abaetetuba, Pará, according to the recommendations of the PNAE. For nutritional adequacy, the average energy consumption (Kcal), carbohydrate (g), protein (g), lipid (g), fiber (g), calcium (mg), iron (mg), magnesium (mg), zinc (mg), vitamin A (μg) and vitamin C (mg) of all the menus by educational category, were compared with the values established in Resolution No.26/2013. Nutrient values above or below the recommendation by the PNAE were considered inadequate. The analyzed menus were nutritionally inadequate, which may contribute to the reduction of school performance and student growth, in addition to dietary uncertainty. The elaborate menus were not nutritionally adequate, demonstrating the need to readjust the recommendations and thus guarantee the Human Right to Adequate Food and consequently the improvement of the learning and school performance.